Canine cutaneous papilloma. Study of seven cases. - KALDRYMIDOU (Ε. ΚΑΛΔΡΥΜΙΔΟΥ), E.; PAPAIOANNOU (Ν. ΠΑΠΑΪΩΑΝΝΟΥ), N.; POUTACHIDIS (Θ. ΠΟΥΤΑΧΙΔΗΣ), Th.; van GARDENER, E.; KARAYANNOPOULOU (Μ. ΚΑΡΑΠΑΝΝΟΠΟΥΛΟΥ), M. (Journal of the Hellenic Veterinary Medical Society, 2018)
Seven cases of canine papilloma were studied histopathologically using light and electron microscopy. Papillomavirus was detected immunohistochemically and by the polymerase chain reaction (PCR) method. The classical squamous papilloma was found in four dogs (#1,2,3,4), the inverted papilloma in one dog (#5) and the fibropapilloma in two dogs (#6,7). Virus particles were detected electromicroscopically in two cases (#1,2). Immunohistochemistry, revealed the presence of the papillomavirus antigen in three cases (#1,2,3). The PCR method resulted in positive for COPV in two cases (#1,2). These results support the view that except for the canine oral papillomavirus, there might be other types of papillomavirus that induce papilloma in dogs.